Ambient‐Temperature All‐Solid‐State Sodium Batteries with a Laminated Composite Electrolyte. (13th May 2020) - Yu, Xingwen; Xue, Leigang; Goodenough, John B.; Manthiram, Arumugam
Abstract: This study presents a sodium‐ion conductive laminated polymer/ceramic‐polymer solid‐state electrolyte for the development of room‐temperature all‐solid‐state sodium batteries. At the negative electrode side, a negative‐electrode‐benign poly(ethylene oxide) (PEO) is used as a polymer matrix into which succinonitrile (SN) is integrated to improve the room‐temperature Na + ‐ion conductivity. At the positive electrode side, a cathode‐friendly poly(acrylonitrile) (PAN) serves as a polymer matrix into which a NASICON‐type ceramic solid‐electrolyte (Na3 Zr2 Si2 PO12 ) powder is incorporated toward both the enhancement of Na + ‐ion conductivity and the prevention of Na dendrite from penetrating through the electrolyte membrane. Through a strategical management of composition, the PAN‐Na3 Zr2 Si2 PO12 ‐NaClO4 composite and the PEO‐SN‐NaClO4 polymer deliver a balanced Na + ‐ion conductivity. Combining the two electrolyte layers, the laminated PEO‐SN‐NaClO4 /PAN‐Na3 Zr2 Si2 PO12 ‐NaClO4 solid electrolyte provides a Na + ‐ion conductivity of 1.36 × 10 −4 S cm −1 at room temperature. With respect to the anodic friendly feature of the PEO‐SN‐NaClO4 layer and the cathodic friendly feature of the PAN‐Na3 Zr2 Si2 PO12 ‐NaClO4 layer, the laminated solid electrolyte presents a stable electrochemical window of 0–4.8 V. Room‐temperature all‐solid‐state sodium batteries fabricated with the laminated solid electrolyte, a Na‐metal negative electrode, and a Na2 MnFe(CN)6 positive electrode exhibit remarkably stable cyclability. Abstract : A rationally designed laminated composite electrolyte PEO‐SN‐NaClO4 /PAN‐Na3 Zr2 Si2 PO12 ‐NaClO4 enables the operation of ambient‐temperature all‐solid‐state sodium batteries with a remarkably stable cycling performance.